A comparison of the suitability of cathode ray tube (CRT) and liquid crystal display (LCD) monitors as visual stimulators in mfERG diagnostics - Kaltwasser, Christoph; Horn, Folkert; Kremers, Jan; Jünemann, Anselm (Documenta Ophthalmologica, 2009)
The aim of this study was to determine up to which extent the specific characteristics of cathode ray tube (CRT) and liquid crystal display (LCD) monitors influence the retinal biosignal when used as stimulators in ocular electrophysiology. In a conventional CRT monitor, each pixel lights up only for a duration of a few milliseconds during each frame. In contrast, liquid crystal displays are quasi-static, i.e. each pixel has a constant luminance during the whole length of the frame, but lights up only with a certain delay after the trigger. These different display characteristics may affect the mfERG signal. The temporal and spatial luminance distributions of a CRT and an LCD monitor were measured in white flashes. The total amount of emitted light was calculated by integration of the intensity versus time curves. By means of an mfERG recording system (RETIsystem, Roland Consult, Brandenburg, Germany) first-order kernel (FOK) mfERG signals were computed and then analysed using customized MATLAB (TheMathWorks, Natick, MA, USA) software. With the two stimulator monitors, differences in the mfERG signal were observed. The latencies of mfERG responses recorded with the LCD monitor were significantly increased by 7.1 ms for N1 and 9.5 ms for P1 compared to the CRT. Due to a higher luminance, the N1 amplitude was significantly higher by approx. 2 dB in measurements with the LCD monitor while no significant difference could be detected with regard to the more contrast sensitive P1 amplitude. When using LCD monitors as stimulators the increase in latencies and differences in the luminance versus time profile must be taken into account. Prior to clinical application, the establishment of guidelines for the use of LCD monitors is recommended.
Keywords: CRT; LCD; Multifocal ERG; Stimulus delivery

Objective perimetry using a four-channel multifocal VEP system: correlation with conventional perimetry and thickness of the retinal nerve fibre layer - Horn, Folkert; Kaltwasser, Christoph; Jünemann, Anselm; Kremers, Jan; Tornow, Ralf-Peter (British Journal of Ophthalmology, 2012)
There is evidence that multifocal visual evoked potentials (VEPs) can be used as an objective tool to detect visual field loss. The aim of this study was to correlate multifocal VEP amplitudes with standard perimetry data and retinal nerve fibre layer (RNFL) thickness.Multifocal VEP recordings were performed with a four-channel electrode array using 58 stimulus fields (pattern reversal dartboard). For each field, the recording from the channel with maximal signal-to-noise ratio (SNR) was retained, resulting in an SNR optimised virtual recording. Correlation with RNFL thickness, measured with spectral domain optical coherence tomography and with standard perimetry, was performed for nerve fibre bundle related areas.The mean amplitudes in nerve fibre related areas were smaller in glaucoma patients than in normal subjects. The differences between both groups were most significant in mid-peripheral areas. Amplitudes in these areas were significantly correlated with corresponding RNFL thickness (Spearman R=0.76) and with standard perimetry (R=0.71).The multifocal VEP amplitude was correlated with perimetric visual field data and the RNFL thickness of the corresponding regions. This method of SNR optimisation is useful for extracting data from recordings and may be appropriate for objective assessment of visual function at different locations.This study has been registered at http://www.clinicaltrials.gov (NCT00494923).
EVALuna2:21033